Links between boreal forest management, soil fungal communities and below‐ground carbon sequestration. (22nd December 2021) - Jörgensen, Karolina; Granath, Gustaf; Strengbom, Joachim; Lindahl, Björn D.
Abstract: Forest management has a potential to alter below‐ground carbon storage. However, the underlying mechanisms, and the relative importance of carbon input and decomposition in regulation of soil carbon dynamics are poorly understood. We examined whether interactive effects of forest fertilization and thinning on carbon stocks in the topsoil of boreal forests were linked to changes in fungal community composition, biomass and enzyme activities, in a long‐term fertilization and thinning experiment distributed across 29 Pinus sylvestris forests along a 1, 300 km latitudinal transect in Sweden. Nitrogen fertilization increased fungal biomass, particularly towards the north and mainly by promoting root‐associated Ascomycetes, but the response was moderated by thinning. Fungal biomass correlated positively with carbon stocks in the organic topsoil. However, ectomycorrhizal Cortinarius species were reduced in abundance by fertilization and correlated negatively with carbon stocks. Plausibly, increased soil carbon stocks after fertilization are linked to increased input of carbon in the form of root‐associated mycelium combined with the loss of ectomycorrhizal decomposers within the genus Cortinarius . These fungal responses to fertilization may mediate a natural climate solution by promoting carbon sequestration in the organic topsoil, but the effect of fertilization may also be undesired from a biodiversity perspective. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.